A tailored LNA clamping design principle: Efficient, economized, specific and ultrasensitive for the detection of point mutations. Issue 10 (29th July 2021) - Yang, Hao; Yan, Mengqiu; Xu, Gaolian; Qian, Xiaohua; Zhao, Ruiying; Han, Yuchen; Zhang, Lin; Gu, Hongchen; Xu, Hong
Abstract: In the development of personalized medicine, the ultrasensitive detection of point mutations that correlate with diseases is important to improve the efficacy of treatment and guide clinical medication. In this study, locked nucleic acid (LNA) was introduced as an amplification suppressor of a massive number of wild‐type alleles in an amplification refractory mutation system (ARMS) to achieve the detection of low‐abundance mutations with high specificity and sensitivity of at least 0.1%. By integrating the length of clamp, base type, number and position of LNA modifications, we have established a "shortest length with the fewest LNA bases" principle from which each LNA base would play a key role in the affinity and the ability of single base discrimination could be improve. Finally, based on this LNA design guideline, a series of the most important single point mutation sites of epidermal growth factor receptor (EGFR) was verified to achieve the optimal amplification state which as low as 0.1% mutation gene amplification was not affected under the wild gene amplification was completely inhibited, demonstrating that the proposed design principle has good applicability and versatility and is of great significance for the detection of circulating tumor DNA. Graphical Abstract and Lay Summary: A "shortest length with the fewest LNA bases" principle in LNA clamping system where the factors such as length, number and position are studied to reach the optimal state. Hence each LNA base would play a key role in the binding affinity, and finally improving the single base discrimination ability of the clamp. In this system the amplification of massive wild‐type gene could be completely suppressed but with almost no influence on a few copies of mutant targets and achieving a detection sensitivity of 0.1%.